Grounding the Stars: Towards an Ecological Astrology - Curry, Patrick (Journal for the study of religion, nature and culture, 2007)
In this paper I seek to outline a conception of astrology in which nature—not a modernist Cartesian nature but the living and sensuous natural world—is central. This involves contextualizing astrology as, in effect, a divinatory practice in which the Earth and its animist apprehension is indispensable. Such a move runs counter to much discourse, both by hostile critics (religious and scientific) and astrologers themselves, which is viewed in Weberian and neo-Weberian terms as part of an attempt, damaging if ultimately unsuccessful, to rationalize and thus disenchant astrology. The positive implications for an openly animist and pluralist astrology are then briefly explored.